2015
DOI: 10.1016/j.ijwd.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Update on lichen planus and its clinical variants

Abstract: Lichen planus (LP) is an inflammatory skin condition with characteristic clinical and histopathological findings. Classic LP typically presents as pruritic, polygonal, violaceous flat-topped papules and plaques; many variants in morphology and location also exist, including oral, nail, linear, annular, atrophic, hypertrophic, inverse, eruptive, bullous, ulcerative, lichen planus pigmentosus, lichen planopilaris, vulvovaginal, actinic, lichen planus-lupus erythematosus overlap syndrome, and lichen planus pemphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
213
2
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(243 citation statements)
references
References 82 publications
6
213
2
22
Order By: Relevance
“…Histologic findings include a lichenoid lymphocytic infiltrate and progressive dermal fibrosis. The disease is often chronic and progressive, and achieving remission is often challenging [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologic findings include a lichenoid lymphocytic infiltrate and progressive dermal fibrosis. The disease is often chronic and progressive, and achieving remission is often challenging [1].…”
Section: Discussionmentioning
confidence: 99%
“…FFA is indistinguishable from classic LPP on trichoscopy and histology, but it has a distinct clinical presentation as a band-like area of alopecia involving the frontal and frontotemporal scalp in postmenopausal Caucasian women. There is also occasional involvement of the eyebrows and eyelashes [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in cancer progression could theoretically be induced by the treatment of active lichen planus or lichen sclerosis. A recent randomized controlled trial demonstrated improvements in the disease course of lichen planus with initial aggressive therapy involving oral prednisolone, with or without additional topical corticosteroids application, and maintenance therapy with weekly low-dose methotrexate when topical therapy was not adequate [13, 14]. The use of immunosuppressive agent is also often mentioned in the literature; however, they bear the risk of increased malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Classic LP typically presents as pruritic, polygonal, purplish papules, and plaques (described using the 6 Ps); many variants in morphology and location also exist, including oral, nail, linear, annular, erosive, atrophic, hypertrophic, inverse, eruptive, bullous, ulcerative, LP pigmentosus, lichen planopilaris, vulvovaginal, actinic, LP-lupus erythematosus overlap syndrome, and LP pemphigoides. [2] Th e sites involved over the skin include the fl exor surfaces of the legs and arms, especially the wrists and elbows. Th e nail beds may also be aff ected with resultant ridging, grooving, pterygium, onychorrhexis, and complete loss of the nail.…”
Section: Introductionmentioning
confidence: 99%